How does psychotherapy work? A case study in multilevel explanation. (8th June 2015) - Roache, Rebecca
Abstract: Multilevel explanations abound in psychiatry. However, formulating useful such explanations is difficult or (some argue) impossible. I point to several ways in which Lane et al. successfully use multilevel explanations to advance understanding of psychotherapeutic effectiveness. I argue that the usefulness of an explanation depends largely on one's purpose, and conclude that this point has been inadequately recognised in psychiatry.